A Prospective Study of High Dose-Rate Brachytherapy or Stereotactic Body Radiotherapy of Intra-Prostatic Recurrence: Toxicity and Long Term Clinical Outcome - Ryg, Una; Seierstad, Therese; Nilsen, Line Brennhaug; Hellebust, Taran Paulsen; Djupvik, Linda Holth; Gustafson, Hilde; Hydal, Jørgen; Kishan, Amar U.; Hole, Knut Håkon; Lilleby, Wolfgang (Frontiers in Oncology, 2022)
Background: Up to half of patients with localized prostate cancer experience biochemical relapse within 10 years after definitive radiotherapy. The aim of this prospective study was to investigate the toxicity, dose to the organs at risk (OARs) and efficacy of dose-intensified focal salvage radiotherapy. Methods and material: Thirty-three patients (median age 68.8 years) with histologically confirmed relapse after primary definitive radiotherapy were enrolled between 2012 and 2019. No patients had metastases at imaging or in bone marrow aspiration. Twenty-three patients were treated with high dose-rate brachytherapy to the recurrent tumor, defined at multiparametric MRI, with 3 fractions of 10Gy with two weeks interval, and 10 patients by stereotactic body radiotherapy with 35Gy to the local recurrence and 25Gy to the whole prostate in 5 fractions. We used the RTOG-scoring system to grade genitourinary (GU) and gastrointestinal toxicity (GI) at three months (acute), and at 12, 24 and 36 months (late). Dose volume histogram parameters to the local recurrence and the OARs were obtained and 2Gy equivalent (EQD2) total dose was calculated using the linear quadratic model with /=3Gy. Efficacy was assessed by the progression-free interval and overall survival. Results: Median follow-up time was 81 months (range 21-115). Six patients had grade 1 acute GI toxicity, none had grade 2 or 3. One patient had grade 3 acute GU toxicity, two had grade 2, and fourteen had grade 1. One patient had late GI toxicity grade 2 and eight had grade 1. Four patients had late GU toxicity grade 2 and eight had grade 1. No patients had grade 3 late toxicity. Mean total D90 to the recurrent tumor was 77.717.0Gy. Mean total rectum D2cc was 17.07.9Gy and mean total urethra D0.1cc was 29.18.2Gy. Twenty-eight patients had re-irradiation without androgen deprivation therapy (ADT). Nine of these are still relapse-free and 10 had a recurrence-free interval longer than 2 years. Conclusion: Toxicity of salvage radiotherapy was mild to moderate. One-third of the patients achieved long-term stable disease without ADT and one-third had a recurrence-free interval longer than 2 years. Some patients progressed rapidly and probably did not benefit from re-irradiation.